Parameter Adjustment for a Dynamic Programming Track-before-Detect-Based Target Detection Algorithm. (16th April 2008) - Nichtern Nichtern, O. O.; Rotman Rotman, S. R. S. R.
Abstract : This paper addresses the problem of tracking a dim moving point target in a sequence of IR images. The proposed tracking system, based on the track-before-detect (TBD) approach, is designed to track and detect dim maneuvering targets from an image sequence under low SNR conditions; a dynamic programming algorithm (DPA) is used to process the frames in the sequence. This paper deals with the practical issues of setting the parameters of our algorithm to maximize tracking capability. In our flexible approach, we are able to accommodate different levels of noise and different target velocities and mobilities. Our algorithm is tested on real data to determine its efficacy.